2010
DOI: 10.1021/es1016119
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of Se and DOC in Soil Solution and Their Relation to Se Bioavailability

Abstract: A 0.01 M CaCl(2) extraction is often used to asses the bioavailability of plant nutrients in soils. However, almost no correlation was found between selenium (Se) in the soil extraction and Se content in grass. The recently developed anion Donnan membrane technique was used to analyze chemical speciation of Se in the 0.01 M CaCl(2) extractions of grassland soils and fractionation of DOC (dissolved organic carbon). The results show that most of Se (67-86%) in the extractions (15 samples) are colloidal-sized Se.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…4A), indicating that there is an association between Se and DOC upon drying. Similar relationship between DOC and soluble Se has been observed using other dried soil samples from grassland (Weng et al, 2011). The absence of a correlation between DOC and soluble Se in the dried samples from potato field can be due to very low level and small range of DOC and soluble Se in the samples.…”
Section: Drying Effect On Soluble Sesupporting
confidence: 77%
See 2 more Smart Citations
“…4A), indicating that there is an association between Se and DOC upon drying. Similar relationship between DOC and soluble Se has been observed using other dried soil samples from grassland (Weng et al, 2011). The absence of a correlation between DOC and soluble Se in the dried samples from potato field can be due to very low level and small range of DOC and soluble Se in the samples.…”
Section: Drying Effect On Soluble Sesupporting
confidence: 77%
“…In the dried clay-peat soil around 3% of sub-nanometer Se measured in the acceptor is probably present as subnanometer organic Se associated with sub-nanometer Hy DOC. Previous DMT analysis using other dried soil samples from grassland has also shown that colloidal sized organic Se accounts for 67 to 86% of total soluble Se in CaCl 2 soil extracts, whereas selenate, selenite and small organic Se molecules account for the remaining 15 to 33% (Weng et al, 2011). The results of DMT analysis indicate that the increase of total soluble Se upon drying is mainly due to the increase of colloidal sized organic Se.…”
Section: Drying Effect On Soluble Sementioning
confidence: 77%
See 1 more Smart Citation
“…Among different Se forms present in soil, soluble Se is the main source available for plant uptake. However, in the soil solution, Se can be present as both inorganic selenate, selenite and as organic Se (Weng et al 2011). Probably not all soluble Se species can be taken up by plants directly.…”
Section: Introductionmentioning
confidence: 99%
“…In soil solution, Se is present as selenate and selenite anions as well as organic Se (Stroud et al, 2012;Tolu et al, 2011;Weng et al, 2011). Soluble selenate and selenite are the major bioavailable chemical forms for plants, although some research showed that selenoamino acids such as selenomethionine and selenocysteine can also be taken up (Abrams et al, 1990b;Kikkert and Berkelaar, 2013;Williams and Mayland, 1992).…”
mentioning
confidence: 99%